2022
DOI: 10.3390/plants12010087
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolic Study of Tamarindus indica L.’s Various Organs Based on GC/MS Analysis, In Silico and In Vitro Anti-Inflammatory and Wound Healing Activities

Abstract: The chemical composition of the n-hexane extract of Tamarindus indica’s various organs— bark, leaves, seeds, and fruits (TIB, TIL, TIS, TIF)—was investigated using gas chromatography-mass spectrometry (GC/MS) analysis. A total of 113 metabolites were identified, accounting for 93.07, 83.17, 84.05, and 85.08 % of the total identified components in TIB, TIL, TIS, and TIF, respectively. Lupeol was the most predominant component in TIB and TIL, accounting for 23.61 and 22.78%, respectively. However, n-Docosanoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Information on the structure-activity relationships of active chemicals that are responsible for the killing action can be obtained by understanding the chemical components of seaweed [ 14 ]. Recently, the dependence on secondary metabolites from natural sources has been in great demand to control various ailments and defense against several conditions [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Information on the structure-activity relationships of active chemicals that are responsible for the killing action can be obtained by understanding the chemical components of seaweed [ 14 ]. Recently, the dependence on secondary metabolites from natural sources has been in great demand to control various ailments and defense against several conditions [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the extracts presented impressive bioactivities, the potent extracts from both the samples were explored for their specific phytochemicals using analytical technique like GC–MS. Various researcher studied plant source extraction using different solvents and were further analyzed using chromatographic techniques like GC–MS, UPLC-ESI-Orbitrap-MS, UPLC-ESI-Q-TOF-MS E , HPLC etc., to observe the presence of important biomolecules that can be utilized to treat inflammatory, wound healing, antioxidants, antimicrobial activity, hepatoprotective activity and so on ( Aly et al, 2023 , Chen et al, 2022a , Djebari et al, 2023 , Razali et al, 2012 , Wang et al, 2022 , Youssef et al, 2023 ). On analysis with GC–MS, it revealed the presence of versatile group of phytocompounds among all the solvent extracts from both the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tamarindus indica tree source is also utilized for medicinal purpose which is a long lived evergreen hardwood tree found in different countries/region, for example, Egypt, Africa (tropical region) and Asia (including India) ( Aly et al, 2023 , Bhadoriya et al, 2011 , Ghaly et al, 2023 ). Tamarindus indica tree yields high amount of green fruits.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue also included important research on the comparative metabolic study of Tamarindus indica (Egypt) from various organs (bark, leaves, seeds, and fruits) and evaluated their anti-inflammatory effects. This study was carried out by Aly et al [11] and concluded that the tested extracts from various organs of T. indica showed considerable anti-inflammatory and wound-healing activities.…”
Section: Middle Eastmentioning
confidence: 99%